Ostatnie dni Plotyna: pandemia i filozofia - Stróżyński, Mateusz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The traditional view of the cause of Plotinus’ death was leprosy. The analysis of the biographical sources, however, point to another hypothesis, that of „Cyprian’s plague”. The last months of Plotinus life and work coincided with the end of this great ancient pandemic and he produced four treatises, focused primarily on ethical problems. The last treatise, On the primal Good (1.7) is a short and concentrated meditation on the First Principle and the soul’s ascent to it.